Retratos de rio : uma etnografia do Jacaré no município de Oliveira, Minas Gerais - Ana Paula Santos Rodrigues (2019)
The Jacaré is a medium-sized river located in the center-west of Minas Gerais and has its first springs located in the municipalities of Oliveira and São Tiago. Passing through seven cities, it flows into the dam of the Furnas hydroelectric. Currently, the river, which is an affluent of the Rio Grande, is very degraded, suffering, mainly, with the silting. This work is an ethnography of Jacaré in the municipality of Oliveira, which aims to understand the relations between the population of Oliveira and the river. It was intended to compose a set of portraits that show the river from the perspective of different people and social groups, who relate to it for different reasons: recreational fishermen, occasional goers, rural producers, state agents, environmentalists, poets. It was sought to understand how these multiplicity of relationships impact on the degradation of the Jacare (or its preservation) and also what ideas of nature are present in the analyzed ethnographic context.